Karaterisasi Biokimia Kandidat Bakteri Endofit Dari Alga Hijau (Ulva lactuca) Sebagai Bioprospeksi Agen Pengendalian Hayati - Kantari, Wulan Wila; ariyanti, dwi (Fakultas Ilmu dan Teknologi Hayati Universitas Teknologi Sumbawa, 2024)
Ulva lactuca or sea lettuce is a green seaweed that is formed like a thin and smooth leaf sheet that has enormous benefits in various fields. One of Ulva lactuca's existence is having endophytic bacteria. Endophytic bacteria are microorganisms that live symbiotically in the tissues of their host plants without causing damage or adverse effects on plants. Endophytic bacteria from Ulva lactuca can have a variety of biochemical activities that have potential as biological control agents against plant pathogens. The study of biochemical characterization of these endophytic bacteria becomes very important to understand the mechanism of their interaction with their host as well as potential applications in biological control. The purpose of this study is to know the results of the characterization of endophytic bacteria isolated from green algae (Ulva lactuca) and to know the results of their biochemical tests. To find out the characterization using morphological characterization methods, gram staining and endospores, and indole tests. While biochemical tests are citrate test, urease test, indole test, and catalase. So that different characterization results are obtained and have diverse morphologies. Biochemical tests of the four candidate isolates of endophytic bacteria found that these endophytic bacteria are suitable for bioprospecting biological control agents. Keywords: 1; Ulva lactuca 2; endophytic bacteria 3; bioprospection of biological control agents